How Perceptual Variables Influence the Behavioral Intention to Use Autonomous Vehicles - Réka Koteczki; Boglárka Eisinger Balassa; Dániel Csikor (Engineering Proceedings)
The rapid development of technology makes the acceptance of autonomous vehicles (AVs) in modern transport a key issue. The aim of the present research was to explore the impact of AVs on behavioral intention to use. An online survey was conducted, in which factors such as perceived usefulness (PU), perceived ease of use (PEU), perceived trust (PT), social influence (SI), and behavioral intention to use (BIU) were investigated. As a result of the investigation, the correlation analysis revealed that there was a significant positive relationship between the intention and all the factors examined. The practical utility of this research is that the results will support developers and vehicle manufacturers in understanding how different social factors influence the adoption of AVs.